Chapter 11: Envisaging the city: roadmap for an interdisciplinary study of urban facescapes - Leone, Massimo (Edward Elgar Publishing, 2024)
The chapter proposes a roadmap for studying the impact of digital technology and artificial intelligence on the presence and meaning of human faces in contemporary cities, with specific attention to the cultural, social and economic role of automatic facial identification and recognition, facial big data and the possibility to generate photo-realistic images of human faces through generative adversarial networks and other algorithms of artificial intelligence. The roadmap situates such inquiry within the study of the long-term relation between cities and faces, in all their multiple facets and manifestations. Investigation in this domain is expected to cast new light on how this fundamental affordance of social interaction, the face, and this essential cradle of human coexistence, the city, are modified after the advent of the digital representation of the face. The planned result is a detailed analysis of contemporary ‘facescapes’, that is, ways in which human faces are turned into support for technological exchange and communicative capital in present-day cities, with specific attention to global urban hubs.